Mapping of Vegetation Coverage: Case Study of Passo Fundo - RS - Costa, Laura Meira; Medeiro, Laís Oliveira de; Neckel, Alcindo; Silva, Thaísa Leal da (Technical and Scientific Journal Green Cities, 2025)
Objective – This article aims to analyze the vegetation cover of the municipality of Passo Fundo-RS using the Normalized Difference Vegetation Index (NDVI) to map the evolution of vegetation in the city, through the Geographic Information System (GIS QGIS) and satellite images. Methodology – Initially, a bibliographic review was carried out on NDVI, vegetation cover and remote sensing, soon after, data collection was carried out using satellite images and GIS QGIS and, finally, the data were analyzed using NVDI maps and a comparison of the NDVI indices 2020 and 2024 of Passo Fundo-RS was carried out. Originality/Relevance – The study addresses the lack of integrated and up-to-date analyses of vegetation cover evolution using accessible geotechnological tools. Thus, the work reinforces the important role of geotechnologies in interdisciplinary scientific production, especially in the fields of geography, urban planning, and environmental sciences. Results – It was possible to verify the situation of the municipality in relation to its vegetation, as well as its evolution in the analyzed period of time and possible factors that influenced both the lack and abundance of vegetation in certain locations. Theoretical/Methodological Contributions – The study demonstrates the effectiveness of the method as a spatial analysis tool, which can be replicated in other urban contexts and reinforces the relevance of environmental indicators as instruments for diagnosing environmental quality and supporting the formulation of public policies. Social and Environmental Contributions – Relevant to urban planning and development, this technique is crucial for developing strategies to improve urban vegetation cover. In this context, it can significantly aid in detecting vegetation changes in environmental quality studies.